Unia Europejska – rozpad czy powrót do równowagi makroekonomicznej i finansowej? Rozważania na temat kryzysu w strefie euro z perspektywy europejskiej i światowej - Walkowski, Maciej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
In 2009 the European Union, and in particular the euro zone, slid into a stage of economic recession on account of the spreading global financial crisis, referred to as ‘2008+.’ Considerable developmental problems are being experienced by the group of countries referred to as PIIGS, particularly by Greece, Spain and Italy, which account for nearly 30% of GDP of the euro zone. Due to the tight developmental interdependencies in the European common market, decreased confidence of global investors, and the consequent potentially lowered profitability of bonds of other Mediterranean economies, the bankruptcy of Greece could cause a domino effect. This could mean serious developmental problems for other indebted Mediterranean economies, such as Italy, Spain and Portugal. It could also drag Germany and France (or their banks, that granted tens of billions of euros in loans to Greece) into financial difficulties, and consequently pose a threat to integration processes throughout Europe. The author of the paper anal zes both the causes and effects of the present financial crisis in the euro zone and presents various scenarios for further developments. He also diagnoses the correctional activities undertaken by selected European governments, the EU and international institutions, their first outcomes, the controversies stirred by the opinions of global rating agencies, and the further developmental prospects for the European Union by 2020.